Association of Bedtime with both Suicidal Ideation and Suicide Planning among Korean Adolescents - Jeong, Wonjeong (Int J Environ Res Public Health, 2019)
Study Objectives: In comparison to other countries, the South Korean population has a short average sleep duration, and studies have suggested that insufficient sleep is a risk factor for suicidal behavior. This study aimed to examine the association of bedtime with suicidal ideation and with suicide planning, respectively, among Korean adolescents. Methods: This study included 48,218 participants from the 2017 Korea Youth Risk Behavior Web-based Survey. Participants were divided into three categories: pre-23:00 bedtime, 23:00–01:30 bedtime, and post-01:30 bedtime. Suicidal ideation and suicide planning were the main dependent variables, and multiple logistic regression analysis was performed to examine the target association. Results: For both male and female respondents, compared to those who had a pre-23:00 bedtime, those whose bedtime was after 01:30 were more likely to have suicidal ideation (post-01:30 bedtime for men: OR = 1.29, 95% CI = 1.16–1.45; for women: OR = 1.32, 95% CI = 1.20–1.44). For suicide planning, the results were also significant for both genders (post-01:30 bedtime for men: OR = 1.41, 95% CI = 1.16–1.70; for women: OR = 1.21, 95% CI = 1.03–1.43). Odds of suicidal ideation were higher for those who had a post-01:30 bedtime on weekdays but not weekends. Conclusions: We found that, among adolescents, going to bed after 01:30 is significantly associated with suicidal ideation and suicide planning, after adjusting for demographic, socioeconomic, and health-related characteristics. Therefore, late bedtime should be the timepoint of a suicide intervention for adolescents, in order to prevent developing suicidal ideations and suicide planning.